Immunotherapy for HER-2 positive breast cancer - Yang, Tingting; Kang, Lihua; Li, Dan; Song, Yanqiu (Frontiers in Oncology, 2023)
Immunotherapy is a developing treatment for advanced breast cancer. Immunotherapy has clinical significance for the treatment of triple-negative breast cancers and human epidermal growth factor receptor-2 positive (HER2+) breast cancers. As an effective use of passive immunotherapy, clinical application of the monoclonal antibodies trastuzumab, pertuzumab and T-DM1 (ado-trastuzumab emtansine) has significantly improved the survival of patients with HER2+ breast cancers. Immune checkpoint inhibitors that block programmed death receptor-1 and its ligand (PD-1 / PD-L1) have also shown benefits in various clinical trials. Adoptive T-cell immunotherapies and tumor vaccines are emerging as novel approaches to breast cancer treatment, but require further study. This article reviews recent advances in immunotherapy for HER2+ breast cancers.